Mosloflavone-Resveratrol Hybrid TMS-HDMF-5z Exhibits Potent In Vitro and In Vivo Anti-Inflammatory Effects Through NF-κB, AP-1, and JAK/STAT Inactivation - Kim, Seo-Yeon; Hassan, Ahmed H.E.; Chung, Kyung-Sook; Kim, Su-Yeon; Han, Hee-Soo; Lee, Hwi-Ho; Jung, Seang-Hwan; Lee, Kwang-Young; Shin, Ji-Sun; Jang, Eungyeong; Yoon, Seolmin; Lee, Yong Sup; et al. (Frontiers in Pharmacology, 2022)
Graphical Abstract